Executives’ unethical behaviour with directions for future research - Zhu, Renhong; Li, Xiaowei; Liu, Qin; Zhou, Qihao (Frontiers in Psychology, 2022)
Executives’ unethical behaviour is a common phenomenon in business practice and a hot topic for academic research, which has a profound negative impact on the healthy development of our economy and society. In the past two decades, several scholars from different disciplines conducted theoretical research and practical explorations on the issue of senior executives’ (un)ethical behaviour and achieved certain research results. However, the existing research in this field still has problems, such as a lack of systematic integration of research results, unclear research hotspots and unclear development directions. Thus, the present study conducts a statistical analysis of 461 research literature on executives’ unethical behaviour published in top Chinese and international journals from 2000 to 2020. By reviewing the progress of existing research topics, this study summarised a research framework of executives’ unethical behaviour from the perspectives of the antecedents, the behaviour itself and the consequences of unethical behaviour. The study further proposed future research trends and recommendations for conducting research on executives’ unethical behaviour under emerging market scenarios. The research results provide new ideas for developing the theory of executives’ unethical behaviour and promote the in-depth development of the research on executives’ unethical behaviour in the context of emerging markets.